PHOTOLUMINESCENCE PROPERTIES OF TB3+ DOPED ON PHOSPHATE GLASS MEDIUM BY ADDITION OF FLUORIDE COMPOUNDS - Simanullang, Elyzabeth; Rajagukguk, Juniastel; Hutahaean, Juniar; Sarumaha, Chayani Setiades (Universitas Negeri Medan, 2024)
Research has been conducted on the effect of the addition of fluoride compounds on the photoluminescence properties of Tb3+ doped on phosphate glass has been found. with the composition of glass samples are 69 P2O5 - 20 LiO2 - 10 AlF3 - 1Tb2O3 (P-Tb1), 59 P2O5 - 20 LiO2 - 10 AlF3 - 10 NaF - 1 Tb2O3 (P-Tb2) and 49 P2O5 - 20 LiO2 - 10 AlF3 - 10 NaF -10KF - 1 Tb2O3 (P-Tb3). All chemical compounds are in powder form with a total mass of 15 grams using the melt-qunching technique at 11000C. To determine the quality of the material, measurements and calculations were made of physical properties including molar mass, density, molar volume, refractive index, Tb3+ ion concentration, Polaron radius, molar refractivity, reflection loss and dielectric constant. Characterizations carried out include FTIR, UV-VIS-NIR Spectrophotometer, Abbe Refractometer, Spectrofluorophotometer. To study the physical properties, the optical properties were examined through their absorption and luminescence spectra. The luminescence spectrum is known by photoluminescence. Characteristic luminescence bands corresponding to electronic transitions of terbium ions were detected under two direct excitations of Tb3+ ions. After 377 nm excitation, the glass sample obtained terbium 5D4→ 7F5 transition at 544 nm indicating green laser. The application of green laser has been investigated with CIE coordinate diagram.